2009
DOI: 10.1021/ja9064415
|View full text |Cite
|
Sign up to set email alerts
|

Indium Tin Oxide Nanoparticles with Compositionally Tunable Surface Plasmon Resonance Frequencies in the Near-IR Region

Abstract: Here we report the synthesis of conducting indium tin oxide (ITO) nanoparticles (NPs) and their surface plasmon resonance (SPR) properties. The SPR peaks of the ITO NPs can be easily tuned by changing the concentration of Sn doping from 3 to 30 mol %. The shortest SPR wavelength of 1618 nm in 10% Sn-doped ITO NPs may reflect the highest electron carrier density in the ITO NPs. The controllable SPR frequencies of metal oxides may offer a novel approach for noble-metal-free SPR applications. Unlike noble-metal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
537
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(556 citation statements)
references
References 23 publications
16
537
2
1
Order By: Relevance
“…18,19 Therefore, it is highly likely that surface plasmons play a significant role in the enhanced Raman signal observed on ITO NRs, similar to what has been extensively reported in metallic nanoparticles. 28 Unlike the 2D ITO systems reported in the literature, our 1D ITO NRs present an extremely high aspect ratio, and this shape factor can be particularly useful for SERS.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…18,19 Therefore, it is highly likely that surface plasmons play a significant role in the enhanced Raman signal observed on ITO NRs, similar to what has been extensively reported in metallic nanoparticles. 28 Unlike the 2D ITO systems reported in the literature, our 1D ITO NRs present an extremely high aspect ratio, and this shape factor can be particularly useful for SERS.…”
supporting
confidence: 71%
“…3,[10][11][12][13] And more recently, other systems involving either a metal oxide thin film or a hybrid system of a metal nanoparticle/metal oxide thin film have been demonstrated as SERS-active materials. 7,[14][15][16][17][18][19] Plasmonic characteristics similar to those observed from noble metals are found in some transparent conducting metal oxides such as indium tin oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide. 18,20 Despite many leading efforts on this aspect, only a small subset of research discusses Raman enhancement effects observed from nanomaterials that are precisely controlled for their physical, chemical, optical, or electrical properties during synthesis.…”
mentioning
confidence: 64%
“…26,95,96 The position of the plasmonic resonance of ITO can be varied from 1600 nm to 2200 nm by controlling the concentration of Sn dopants (see Fig. 7a-c) 95,97 or electrochemically by applying a bias voltage (Fig.…”
Section: Tin Doped Indium Oxide (Ito)mentioning
confidence: 99%
“…A variety of thin film coating materials and technologies have been studied in academia and industry including rare-earth hexaborides, 2 indium tin oxides, 3,4 antimony-doped tin oxides, 5 and Low-E glasses. 6 However, ideal NIR absorbents are still in high demand due to the limitations of current technologies, such as low visible light transparency, 2 partial NIR shielding, 3,4 and high cost of material or processing.…”
Section: Introductionmentioning
confidence: 99%